Tailored Heat Treated Profiles - Enhancement of the Forming Limit of Aluminum Profiles under Bending Load - Merklein, Marion; Lechner, Michael; Schneider, Thomas; Plettke, Raoul (Key Engineering Materials, 2012)
Aluminum profiles are well-established components in lightweight constructions. However, these profiles have a small forming capability in comparison to steel profiles, which leads to a limitation in their application. Within this paper a new and innovative approach for the enhancement of the forming limit of aluminum profiles under bending load called Tailored Heat Treated Profiles (THTP) is presented. With THTP the mechanical properties of the material are locally modified by a short-term heat treatment. By this local modification the material flow during the following cold bending operation can be influenced. For the design of the heat treatment layout, the correlation between the heat treatment parameters and the material properties has to be investigated. Tensile specimens were cut out of the profile and were subsequently completely heat treated with a laser. The changes of the mechanical properties caused by the heat treatment were analyzed by tensile tests. However, with a complete softening of the profile, the formability could not be improved. To increase the formability a local heat treatment, which leads to partial softening of the profile, has to be investigated. In order to characterize the heat-affected zone (HAZ) of the laser treatment, thermal camera and microhardness measurements were carried out. Appropriate heat treatment layouts have to be found to enhance the forming limit. Different layout strategies were developed and afterwards validated by the heat treatment and forming of profiles. This paper will present the findings of this investigation and show that THTP can be used to improve the formability of aluminum profiles for bending operations. © (2012) Trans Tech Publications.
LFT Import::2019-07-29 (1801)
Keywords: Aluminum profiles; Bending; Enhancement of formability; Tailored heat treatment